2014
DOI: 10.1371/journal.pone.0105373
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Mediated Chemical Changes in Rice Plants Impact the Relationship between Non-Vector Planthopper Nilaparvata lugens Stål and Its Egg Parasitoid Anagrus nilaparvatae Pang et Wang

Abstract: In order to clarify the impacts of southern rice black-streaked dwarf virus (SRBSDV) infection on rice plants, rice planthoppers and natural enemies, differences in nutrients and volatile secondary metabolites between infected and healthy rice plants were examined. Furthermore, the impacts of virus-mediated changes in plants on the population growth of non-vector brown planthopper (BPH), Nilaparvata lugens, and the selectivity and parasitic capability of planthopper egg parasitoid Anagrus nilaparvatae were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Although those differences between responses of vectors and nonvectors to viral infection have been poorly studied until now, some studies have shown similar patterns. The PT circulative SRBSDV infection on rice plants had no effect on a planthopper nonvector (He et al ., ) but affected its vector (Tu et al ., ). A positive correlation was also highlighted between the NPT noncirculative PVY transmission efficiency by five aphid species (from nonvector to efficient ones) and the duration of their phloem sap ingestion phases (Boquel et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although those differences between responses of vectors and nonvectors to viral infection have been poorly studied until now, some studies have shown similar patterns. The PT circulative SRBSDV infection on rice plants had no effect on a planthopper nonvector (He et al ., ) but affected its vector (Tu et al ., ). A positive correlation was also highlighted between the NPT noncirculative PVY transmission efficiency by five aphid species (from nonvector to efficient ones) and the duration of their phloem sap ingestion phases (Boquel et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the relationship between alteration of colonization by the vector on infected plants and vector virus‐transmission efficiency. For example, the PT circulative Southern rice black‐streaked dwarf virus (SRBSDV, Fijivirus ) infection on rice plants had no effects on a nonvector brown planthopper (BPH, Nilaparvata lugens ) (He et al ., ) but affected its vector, the white‐backed planthopper (WBPH, Sogatella furcifera ) (Tu et al ., ). Boquel et al .…”
Section: Introductionmentioning
confidence: 99%
“…The healthy plants become their main food source and habitat. Some studies have indicated that the lifespans of female BPHs are shortened in SRBSDV-infected rice plants44. The lifespan of WBPHs carrying SRBSDV is less than 15 days at 25 °C45.…”
Section: Discussionmentioning
confidence: 99%
“…However, planthoppers and leafhoppers of the family Delphacidae are highly specific as to which viruses they acquire and/or transmit (Milne et al, 2005). For example, the brown planthopper has been found to feed on SRBSDV-infected plants without any impact on insect biology, and the virus could not be detected by RT-PCR (Pu et al, 2012;He et al, 2014). Similarly, corn stunt spiroplasm has not been detected in Peregrinus maidis after feeding on infected corn plants (Vega et al, 1995).…”
Section: Discussionmentioning
confidence: 99%